UV (ultraviolet) film coating process for anti-counterfeit label

By using supercritical carbon dioxide cleaning, electrospinning and laser induced curing technologies in the UV coating process of anti-counterfeiting labels, nanofiber composite films are prepared, which solves the problem of insufficient strength and anti-counterfeiting characteristics of anti-counterfeiting label materials in the prior art, achieves higher anti-counterfeiting performance and durability, and improves the accuracy of production efficiency and quality detection.

CN119502587APending Publication Date: 2025-02-25JIANGSU HENGDA LASER IMAGE CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411541114.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When the UV coating process of the existing anti-counterfeiting label is used in harsh environments, the material strength, toughness and anti-counterfeiting characteristics are insufficient, and it is easy to scratch in high friction environments, resulting in blurred label information, and anti-counterfeiting methods are easily copied or imitated, making it difficult to provide sufficient information and complexity.

Method used

Supercritical carbon dioxide cleaning technology, electrospinning technology and laser induced curing technology were used to prepare composite films with nanofiber structures, and combined with UV curing coating agents, and quality detection was carried out through quantum dot spectral analysis and on-site picture acquisition comparison technology.

Benefits of technology

It significantly improves the anti-counterfeiting performance and durability of the label, enhances mechanical strength and flexibility, hinders the replication of imitations, provides multiple functions such as waterproof, oilproof, UV resistance, and improves the accuracy of production efficiency and quality inspection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119502587A_ABST
    Figure CN119502587A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of UV film coating, and discloses an anti-counterfeit label UV film coating process which comprises the following operation steps: S1, early-stage preparation: a, surface preparation; b, preparing materials; and c, replacing a UV curing machine structure. The performance of the composite film in the aspects of tear resistance and wear resistance is far better than that of a traditional label material, and the composite film can be kept intact in a severe environment; besides, the label can resist erosion of various chemical substances due to the chemical stability of PVDF, so that the label still keeps excellent performance in a humid environment or an environment in contact with chemicals, and the application range of the label is expanded; in the aspect of functionality, the UV curing film coating agent and the composite film are combined, so that the label not only has a basic anti-counterfeiting function, but also can realize multiple functions of water resistance, oil resistance, ultraviolet resistance and the like, and meanwhile, the production efficiency is optimized and the production time is shortened due to the rapid reaction characteristic of the UV curing technology; the combination process of the nanofiber membrane prepared through electrospinning and the UV coating film is more efficient and smoother, and the use effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of UV laminating, and in particular relates to a UV laminating process for an anti-counterfeiting label. Background Art

[0002] The UV lamination process of anti-counterfeiting labels is a process that uses ultraviolet (UV) light curing technology to protect and enhance the surface of anti-counterfeiting labels. Usually, the label pattern is printed on the base paper, the UV laminating material is evenly coated, and the laminating material is quickly cured by UV light source to form a hard protective layer.

[0003] The UV lamination process of anti-counterfeiting labels in the prior art usually uses specific polymer materials. These materials may have certain limitations in strength, toughness, air permeability and barrier properties, which limits the application of anti-counterfeiting labels in harsh environments, and traditional materials may not be able to provide sufficient anti-counterfeiting features, such as special optical effects or electrical properties, making the anti-counterfeiting means relatively single and prone to scratches in high-friction environments, resulting in blurred label information and affecting the anti-counterfeiting effect. In addition, the UV lamination process of existing anti-counterfeiting labels mainly relies on the printing effect of UV ink and the physical properties of the lamination layer (such as gloss, thickness, transparency, etc.) for anti-counterfeiting. However, these anti-counterfeiting means are relatively easy to copy or imitate. A single anti-counterfeiting means may not provide enough information and complexity, making the anti-counterfeiting label easy to crack or forge, and the actual use effect is not good. Summary of the invention

[0004] The purpose of the present invention is to provide a UV laminating process for anti-counterfeiting labels to solve the problems raised in the above background technology.

[0005] In order to achieve the above object, the present invention provides the following technical solution: a UV laminating process for anti-counterfeiting labels, comprising the following operating steps:

[0006] S1. Preliminary preparation: a. surface preparation; b. material preparation; c. replacement of UV curing machine structure;

[0007] Use supercritical carbon dioxide cleaning technology to clean the label surface; prepare UV curing coating agent; use aluminum-magnesium alloy with high UV reflectivity as the reflector, and replace it with UVB (wavelength 280-315nm) lamp tube;

[0008] S2, coating and laminating: a. laminating preparation; b. coating UV curing laminating agent;

[0009] The composite film is prepared by electrospinning technology, and the composite film is laminated on the top of the label substrate by applying a UV curable laminating agent;

[0010] S3. Curing treatment: Use laser induced curing technology to cure the coated product.

[0011] S4. Quality inspection: Use quantum dot spectrum analysis technology and on-site image acquisition and comparison technology to conduct quality inspection on the surface of the cured sample. The specific inspection parameters are: flatness, glossiness, color and anti-counterfeiting effect.

[0012] Preferably, in S1, the supercritical carbon dioxide (SC-CO2) cleaning technology uses the solubility and permeability of carbon dioxide in a supercritical state to dissolve and remove pollutants (such as grease, dust, etc.) on the surface of the label. The pressure range of the supercritical carbon dioxide (SC-CO2) cleaning technology is 7.38-9.25MPa, and the temperature is 31.1-45.8°C, ensuring that it becomes a supercritical fluid state. The cleaning time of supercritical carbon dioxide (SC-CO2) cleaning is 15-25min.

[0013] Preferably, in S1, the prepared UV curable coating agent includes a photoinitiator, a plasticizer, a leveling agent and a basic adhesive, the photoinitiator is benzoin ethyl ether, the plasticizer is dibutyl phthalate, the leveling agent is a silicone acrylate compound, and the basic adhesive is a polyurethane acrylate resin.

[0014] Preferably, in S2, the preparation of the composite membrane by electrospinning technology includes preparation of a polymer solution, electrospinning to obtain fibers and composite treatment, the polymer solution is polyvinylidene fluoride (PVDF), the modulated polymer solution is transferred to the nozzle of the electrospinning equipment, the electrospinning equipment is turned on, the polymer solution is formed into nanofibers under the action of a high voltage electric field, and deposited on a collecting device to form a thin film, the nanofiber film is collected, and the nanofiber film is bonded to an ordinary film with an adhesive to obtain a composite film.

[0015] Preferably, in S2, the composite film is assembled on a curing machine, and the prepared UV curing laminating agent is coated on the top of the transported label substrate by a roller type, and bonded to the composite film to complete the coating and laminating operations.

[0016] Preferably, in S3, the laser in the laser induced curing technology adopts a CO2 laser, and the scanning curing parameters of the laser CO2 laser include: output power, scanning speed and spot size, the output power is 20-50W, the scanning speed is 20mm / s-100mm / s, and the spot size is 20μm-200μm.

[0017] Preferably, in S4, in the quantum dot spectral analysis technology, when quantum dots are excited by energy, they emit light of a specific wavelength, and the spectral characteristics emitted by the quantum dots are detected to obtain the composition, size and morphology information of the quantum dots, and perform quality identification of the anti-counterfeiting in the anti-counterfeiting label.

[0018] Preferably, in S4, a high-definition image of the cured product is obtained by on-site image acquisition, and the image information is input into a large database stored in a computer, compared with the surface state of the standard product, and the abnormal points of the image are analyzed to complete the standard quality inspection.

[0019] The beneficial effects of the present invention are as follows:

[0020] 1. The present invention significantly improves the anti-counterfeiting performance of the label by utilizing the nanofiber structure generated by electrospinning technology. Its unique microstructure and large specific surface area effectively hinder the replication of imitation products. Secondly, PVDF nanofibers have excellent mechanical strength and flexibility, which enhances the durability of the label in daily use, making the composite film far superior to traditional label materials in terms of tear resistance and wear resistance, and can remain intact in harsh environments. In addition, the chemical stability of PVDF enables the label to resist the erosion of a variety of chemical substances, thereby maintaining excellent performance in a humid or chemically exposed environment, expanding its application range. In terms of functionality, the combination of UV curing coating agent and composite film makes the label not only have basic anti-counterfeiting functions, but also realize multiple functions such as waterproof, oil-proof, and UV resistance. At the same time, the rapid response characteristics of UV curing technology optimize production efficiency and reduce production time, making the combination process of the nanofiber membrane prepared by electrospinning and the UV coating more efficient and smooth, and the use effect is good.

[0021] 2. The present invention uses a CO2 laser in the UV lamination process of the anti-counterfeiting label to optimize the curing parameters such as output power, scanning speed and spot size, which can effectively improve the curing efficiency and uniformity of the coating, thereby significantly enhancing the scratch resistance and chemical corrosion resistance of the label, ensuring the clear presentation of fine anti-counterfeiting features such as QR codes, patterns and other details. This technology not only improves the overall anti-counterfeiting performance of the label, but also ensures its stability and durability in various environments, thereby enhancing consumers' trust in the brand. The laser curing process has higher production efficiency than traditional methods, can shorten the production cycle, reduce production costs, and enable enterprises to gain greater advantages in market competition. The adaptability of the CO2 laser enables it to be widely used in a variety of materials, providing more possibilities for the diversified design of anti-counterfeiting labels, and providing a reliable solution to meet the market demand for high-quality, anti-counterfeiting labels, with good use effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the process flow of the present invention;

[0023] Figure 2 The figure is a schematic diagram of the process of preparing the coating according to the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] like Figure 1 to Figure 2 As shown, the embodiment of the present invention provides a UV laminating process for an anti-counterfeiting label, comprising the following steps:

[0026] S1. Preliminary preparation: a. surface preparation; b. material preparation; c. replacement of UV curing machine structure;

[0027] Use supercritical carbon dioxide cleaning technology to clean the label surface; prepare UV curing coating agent; use aluminum-magnesium alloy with high UV reflectivity as the reflector, and replace it with UVB (wavelength 280-315nm) lamp tube;

[0028] S2, coating and laminating: a. laminating preparation; b. coating UV curing laminating agent;

[0029] The composite film is prepared by electrospinning technology, and the composite film is laminated on the top of the label substrate by applying a UV curable laminating agent;

[0030] S3. Curing treatment: Use laser induced curing technology to cure the coated product.

[0031] S4. Quality inspection: Use quantum dot spectrum analysis technology and on-site image acquisition and comparison technology to conduct quality inspection on the surface of the cured sample. The specific inspection parameters are: flatness, glossiness, color and anti-counterfeiting effect.

[0032] The reflective cover improves the efficiency of UV light, and the reaction efficiency of the photoinitiator is improved, thereby improving the cross-linking effect.

[0033] Among them, in S1, the supercritical carbon dioxide (SC-CO2) cleaning technology uses the solubility and permeability of carbon dioxide in a supercritical state to dissolve and remove pollutants (such as grease, dust, etc.) on the surface of the label. The pressure range of the supercritical carbon dioxide (SC-CO2) cleaning technology is 7.38-9.25MPa, and the temperature is 31.1-45.8℃, ensuring that it becomes a supercritical fluid state. The cleaning time of supercritical carbon dioxide (SC-CO2) cleaning is 15-25min.

[0034] Supercritical carbon dioxide has excellent solubility and permeability, and can effectively remove pollutants (such as grease, dust, etc.) on the surface of the label. In the supercritical state, the density of carbon dioxide is close to that of liquid, while the viscosity is close to that of gas, which enables it to penetrate into the subtle surface structure and effectively remove pollutants. When using it, the pressure (7.38-9.25MPa) and temperature (31.1-45.8℃) are strictly controlled to ensure that the carbon dioxide can remain in the supercritical state to achieve the best cleaning effect. The cleaning time is controlled within 15-25 minutes. Too long may cause deformation or damage to the material, and too short may not completely remove the pollutants. This time period has a better cleaning effect.

[0035] The specific effects are: compared with traditional cleaning agents, SC-CO2 is an environmentally friendly cleaning medium that will not pollute the environment and leaves no residue after cleaning, meeting modern environmental protection requirements; the mild nature of SC-CO2 reduces the risk of damage to label materials, especially for the protection of fine patterns and fragile materials; the clean surface provides a good foundation for subsequent coating and curing processes, ensuring the adhesion and final effect of the UV curing laminating agent.

[0036] The surface cleanliness of labels cleaned by SC-CO2 is significantly improved, which can effectively enhance the adhesion of UV laminating agents and ultimately improve the flatness and glossiness of the product. The clean surface helps to improve the anti-counterfeiting effect, making it easier to identify and detect possible defects during subsequent quality inspections.

[0037] Among them, in S1, the prepared UV curing coating agent includes a photoinitiator, a plasticizer, a leveling agent and a basic adhesive, the photoinitiator is benzoin ethyl ether, the plasticizer is dibutyl phthalate, the leveling agent is a silicone acrylate compound, and the basic adhesive is a polyurethane acrylate resin.

[0038] The proportions of the photoinitiator, the plasticizer, the leveling agent and the basic adhesive are 3%-5%, 10%-15%, 1%-3% and 80%-85% respectively.

[0039] Photoinitiators can quickly decompose under UV light to produce free radicals, thereby initiating the curing reaction of the resin. Benzoin ethyl ether has good sensitivity and reactivity in UV curing and is suitable for thin film coatings to ensure the high efficiency and rapidity of UV curing reactions, reduce curing time, and improve production efficiency. Plasticizers are used to improve the flexibility and processability of the coating, making the coating more durable and less prone to cracking, improving the mechanical properties and durability of the label, especially when applied to surfaces that are easily bent or deformed, to enhance the service life of the label. Leveling agents are used to reduce the unevenness of the coating surface, improve the appearance after coating, prevent surface defects, ensure the flatness and smoothness of the coating, enhance the visual effect of the label, and enhance its market appeal. Polyurethane acrylate resin is used as the main adhesive to ensure good bonding between the coating layer and the label substrate, improve adhesion, and provide strong bonding force, so that the coating layer is not easy to peel off during use, ensuring the stability of the anti-counterfeiting effect.

[0040] Among them, in S2, the preparation of composite membrane by electrospinning technology includes preparation of polymer solution, electrospinning to obtain fiber and composite treatment. The polymer solution is polyvinylidene fluoride (PVDF). The modulated polymer solution is transferred to the nozzle of the electrospinning equipment, and the electrospinning equipment is turned on to make the polymer solution form nanofibers under the action of the high voltage electric field, and deposited on the collecting device to form a film. The nanofiber film is collected, and the nanofiber film is bonded to the ordinary film with an adhesive to obtain a composite film. The composite film is assembled on a curing machine, and the prepared UV curing coating agent is coated on the top of the transported label substrate by a roller type, and bonded to the composite film to complete the coating and laminating operations.

[0041] Polyvinylidene fluoride (PVDF) is a polymer material with excellent chemical stability and mechanical properties. It is suitable for composite films of anti-counterfeiting labels. The preparation of high-concentration PVDF solution is the basis for subsequent electrospinning, which affects the quality and performance of the final nanofibers. The existing coating materials ensure good compatibility and adhesion with the electrospun film.

[0042] The electrospinning equipment includes a high-voltage power supply, a nozzle, and a collecting device. The polymer solution also needs to be added with an appropriate amount of additives, such as anti-ultraviolet agents and antibacterial agents.

[0043] The specific operation of electrospinning is:

[0044] The prepared polymer solution is transferred into a needle equipped with a pressure sensor and a flow control device;

[0045] Turn on the high-voltage power supply of the device, adjust the distance between the nozzle and the collecting device and the flow rate of the solution, so that the polymer solution forms nanofibers under the action of the high-voltage electric field and is deposited on the collecting device;

[0046] The diameter, morphology and distribution of nanofibers can be controlled by adjusting the process parameters.

[0047] The nanofibers generated by electrospinning technology have a large specific surface area and unique microstructure, which can effectively hinder the copying of counterfeits, not only increasing the complexity of the label, but also increasing the difficulty of consumer identification; PVDF nanofibers have excellent mechanical strength and flexibility, which enhances the durability of the label in daily use. Compared with traditional label materials, the composite film performs better in tear resistance and abrasion resistance, and can maintain integrity in harsh environments; and can resist corrosion from a variety of chemicals. This allows the label to maintain its performance in a humid or chemically exposed environment, increasing its application range; the rapid response characteristics of UV curing technology make the laminating process efficient and reduce production time. The combination of nanofiber membranes prepared by electrospinning and UV laminating makes the entire production process smoother.

[0048] Among them, in S3, the laser in the laser induced curing technology adopts CO2 laser, and the scanning curing parameters of the laser CO2 laser include: output power, scanning speed and spot size. The output power is 20-50W, the scanning speed is 20mm / s-100mm / s, and the spot size is 20μm-200μm.

[0049] The application of CO2 laser in UV coating process has important improvement significance: CO2 laser can produce high-intensity beam, which is suitable for rapid curing of polymers. Its long wavelength (10.6μm) can be effectively absorbed by UV coating, thus achieving efficient curing; CO2 laser is suitable for a variety of materials.

[0050] The output power determines the energy density of the laser and affects the speed and effect of curing. The set power can ensure that the coating is fully cured within a reasonable time to avoid uncured residues. Too high power may cause thermal damage to the material, while too low power may lead to incomplete curing, affecting the durability and anti-counterfeiting effect of the label. The scanning speed affects the contact time between the laser and the material surface. The scanning speed can ensure uniform curing and avoid local overheating. Too fast speed may lead to insufficient curing, while too slow speed may cause heat accumulation, affecting the appearance and performance of the label. The spot size affects the energy distribution of the laser. A spot size of 20μm-200μm can achieve higher resolution and fine curing effects.

[0051] Among them, in S4, when the quantum dots in the quantum dot spectral analysis technology are excited by energy, they emit light of a specific wavelength, and detect the spectral characteristics of the quantum dots to obtain the composition, size and morphology information of the quantum dots, and perform quality identification on the anti-counterfeiting in the anti-counterfeiting label. The high-definition image of the solidified product is obtained by on-site image collection, and the image information is input into a large database stored in the computer, compared with the surface state of the standard product, and the abnormal points of the image are analyzed to complete the standard quality inspection.

[0052] Quantum dots emit light at specific wavelengths, which can provide high-resolution spectral features, making it easy to accurately identify the authenticity of labels. This uniqueness makes it highly anti-counterfeiting in the market, and by analyzing the composition and morphology of quantum dots, quality monitoring can be performed during the production process to ensure that each batch of products meets standard requirements; using on-site high-definition image acquisition, it is possible to monitor the production status in real time and quickly discover problems. By inputting the image information collected on-site into a large computer database and comparing it with standard products, it is possible to effectively identify potential quality anomalies. Digital management not only improves detection efficiency, but also provides a basis for subsequent quality traceability.

[0053] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A UV laminating process for anti-counterfeiting labels, characterized by: The steps include: S1. Preliminary preparation: a. Surface preparation; b. Material preparation; c. Replace the UV curing machine structure; Use supercritical carbon dioxide cleaning technology to clean the label surface; Prepare a UV curing coating agent; use an aluminum-magnesium alloy with a high UV reflectivity as a reflector, and replace it with a UVB (wavelength 280-315nm) lamp tube; S2, coating and laminating: a. laminating preparation; b. coating UV curing laminating agent; The composite film is prepared by electrospinning technology, and the composite film is laminated on the top of the label substrate by applying a UV curable laminating agent; S3. Curing treatment: Use laser induced curing technology to cure the coated product. S4. Quality inspection: Use quantum dot spectrum analysis technology and on-site image acquisition and comparison technology to conduct quality inspection on the surface of the cured sample. The specific inspection parameters are: flatness, glossiness, color and anti-counterfeiting effect.

2. The UV laminating process for anti-counterfeiting labels according to claim 1, characterized in that: In S1, the supercritical carbon dioxide (SC-CO2) cleaning technology uses the solubility and permeability of carbon dioxide in a supercritical state to dissolve and remove pollutants (such as grease, dust, etc.) on the surface of the label. The pressure range of the supercritical carbon dioxide (SC-CO2) cleaning technology is 7.38-9.25MPa, and the temperature is 31.1-45.8°C, ensuring that it becomes a supercritical fluid state. The cleaning time of supercritical carbon dioxide (SC-CO2) cleaning is 15-25min.

3. The UV laminating process for anti-counterfeiting labels according to claim 2, characterized in that: In S1, the prepared UV curable coating agent includes a photoinitiator, a plasticizer, a leveling agent and a basic adhesive, the photoinitiator is benzoin ethyl ether, the plasticizer is dibutyl phthalate, the leveling agent is a silicone acrylate compound, and the basic adhesive is a polyurethane acrylate resin.

4. The UV laminating process for anti-counterfeiting labels according to claim 1, characterized in that: In S2, the preparation of the composite membrane by electrospinning technology includes preparation of polymer solution, electrospinning to obtain fibers and composite treatment, the polymer solution is polyvinylidene fluoride (PVDF), the modulated polymer solution is transferred to the nozzle of the electrospinning equipment, the electrospinning equipment is turned on, the polymer solution is formed into nanofibers under the action of a high voltage electric field, and deposited on a collecting device to form a film, the nanofiber film is collected, and the nanofiber film is bonded to an ordinary film with an adhesive to obtain a composite film.

5. The UV laminating process for anti-counterfeiting labels according to claim 4, characterized in that: In S2, the composite film is assembled on a curing machine, and the prepared UV curing laminating agent is coated on the top of the transported label substrate by a roller method and bonded to the composite film to complete the coating and laminating operations.

6. The UV laminating process for anti-counterfeiting labels according to claim 1, characterized in that: In S3, the laser in the laser induced curing technology adopts a CO2 laser, and the scanning curing parameters of the laser CO2 laser include: output power, scanning speed and spot size. The output power is 20-50W, the scanning speed is 20mm / s-100mm / s, and the spot size is 20μm-200μm.

7. The UV laminating process for anti-counterfeiting labels according to claim 1, characterized in that: In S4, when quantum dots in quantum dot spectral analysis technology are excited by energy, they emit light of a specific wavelength, and the spectral characteristics emitted by the quantum dots are detected to obtain the composition, size and morphology information of the quantum dots, and to perform quality identification of the anti-counterfeiting in the anti-counterfeiting label.

8. The UV laminating process for anti-counterfeiting labels according to claim 7, characterized in that: In S4, a high-definition image of the cured product is obtained by on-site image acquisition, and the image information is input into a large database stored in a computer, compared with the surface state of the standard product, and the abnormal points of the image are analyzed to complete the standard quality inspection.

Citation Information

Patent Citations

  • Anti-counterfeiting identification method by aid of quantum points

    CN102693679A

  • Manufacture method of anti-counterfeiting label

    CN109712517A

  • Preparation method of micro-nano structure anti-counterfeit label

    CN109754043A

  • Aluminum-plastic composite film for packaging anti-counterfeiting suppository and preparation method thereof

    CN110936688A

  • Environment-friendly anti-counterfeit label packaging and printing process

    CN117565578A